2013
DOI: 10.1155/2013/612739
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase Inhibitory Effect and Antioxidative Activities of Fermented and Ethanol Extracts of Rhodiola rosea and Lonicera japonica

Abstract: This is the first study to investigate the biological activities of fermented extracts of Rhodiola rosea L. (Crassulaceae) and Lonicera japonica Thunb. (Caprifoliaceae). Alcaligenes piechaudii CC-ESB2 fermented and ethanol extracts of Rhodiola rosea and Lonicera japonica were prepared and the antioxidative activities of different concentrations of samples were evaluated using in vitro antioxidative assays. Tyrosinase inhibition was determined by using the dopachrome method with L-DOPA as substrate. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Previous reports have shown that tyrosinase might also be involved in neuromelanin production and be associated with Parkinson's disease (Chen et al . ). Therefore, inhibiting tyrosinase activity is applicable to skin‐lightening and in preventing neurodegeneration (Kwon et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous reports have shown that tyrosinase might also be involved in neuromelanin production and be associated with Parkinson's disease (Chen et al . ). Therefore, inhibiting tyrosinase activity is applicable to skin‐lightening and in preventing neurodegeneration (Kwon et al .…”
Section: Introductionmentioning
confidence: 97%
“…Although a broad spectrum of α‐glucosidase and tyrosinase inhibitors, including ascorbic acid and phenolic compounds (Chen et al . ), have been obtained from natural products (Kim and Uyama ), there is still need to explore the microbial world for pioneering and more effective classes of effective antioxidants, α‐glucosidase and tyrosinase inhibitors from LAB due to their being Generally Recognized As Safe (GRAS).…”
Section: Introductionmentioning
confidence: 99%
“…These potential green products are developed from a bacterial strain named Alcaligenes piechaudii CC-ESB2, which with higher emulsification activity, hydrophobicity and biosurfactant-producing characteristics, is a hydrocarbon-biodegrading bacterium isolated from oil-contaminated soil (1). The role of A. piechaudii CC-ESB2 fermented solution was reported earlier by Chen et al (2) in enhancing the antioxidative activities of Chinese medicinal herbs including Rhodiola rosea and Lonicera japonica Thunb. Therefore, in this study A. piechaudii CC-ESB2 is used to ferment with CMHs including Monascus purpureus (M), Spirulina platensis (S), L. japonica Thunb (L), R. rosea (R), Cassia nomame (C), Garcinia cambogia (G), Opuntia dillenii (Ker), Haw (O), and Phaseolus vulgaris (P).…”
mentioning
confidence: 92%
“…Previous reports have shown that tyrosinase might also be involved in neuromelanin production and be associated with Parkinson's disease (Chen et al, 2013). Therefore, inhibiting tyrosinase activity is applicable to skin-lightening and in preventing neurodegeneration (Kwon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%